Hybrid capital instruments in the financial industry - Sebastian Salzmann; Ernst Fahling (ISM Research Journal, 2016)
The number and issuances of hybrid capital instruments are growing, especially since the introduction of regulatory capital requirements by the Basel Accords in 1988. This paper analyses the major developments in the hybrid capital market. As the largest issuer of hybrid capital this paper focuses on the financial industry. The main driver behind the market developments is regulatory capital requirements and a major constraint for market growth is the credit rating. Statistical tests accept the hypothesis that rated banks are more likely to issue hybrid capital than banks without a credit rating. Furthermore the level of the Tier 1 ratio has a huge influence on the type of hybrid security, which is issued to fulfil the regulatory capital requirements.
Keywords: 650